IMPLEMENTATION OF COLLECTION OF NAD LOANS THROUGH AUCTION ON LIABILITY RIGHTS AS GUARANTEE IN PT. BPD SUMATERA BARAT - Umul Khair; Ana Ramadhona; Edi Rosman (Jurnal Cendekia Hukum, 2022)
Basically, the granting of credit facilities can be done by anyone, as long as the person concerned has the ability to do so, through a loan agreement between the lender (creditor on the one hand) and the loan recipient (debtor on the other). However, in practice, the debtor always agrees to the loan agreement by the creditor even though the interest is very high. In order to guarantee the interests of the bank, the debtor is required to provide a guarantee/collateral to the bank PT. BPD West Sumatra is one of the banks that implement auctions as a way of resolving non-performing loans. The Bank will submit an auction to be executed by the State Property and Auction Service Office (KPKNL). So the procedure for settling bad loans through auctions at PT. BPD West Sumatra for example at Bank Nagari Payakumbuh Branch has complied with other banking regulations guided by the Regulation of the Minister of Finance in particular Article 6 and Article 20, as well as Regulation of the Minister of Finance No. 106/PMK.06/2013 concerning Amendments to the Regulation of the Minister of Finance No. 93/PMK.06/2010 concerning Instructions for Implementation of Auctions, and the object of Collateral that can be processed for auction is collateral that has been installed with Mortgage through the Office of the State Assets and Auction Service (KPKNL).